THEOLOGICAL DIMENSIONS IN MEMITU RITUALS IN CIREBON - B Busro; Ai Yeni Yuliyanti; Abdul Syukur; Rifki Rosyad (Patanjala: Journal of Historical and Cultural Research, 2020)
Indonesia is very famous for its rich culture. Cirebon as one of the districts in West Java is also very thick with its culture. This article discusses one of the cultures in Kedungsana Village Cirebon, the phenomenon of ritual slametan Memitu. The purpose of this study is to examine the practice of ritual slametan Memitu carried out by Kedungsana community together with its theological dimensions. The research subjects were the community of Kedungsana Village, Plumbon District, Cirebon Regency. The process of collecting data through direct observation and to get deep information in interviews, we use a purposive sampling technique. The results of the study found that the purpose of carrying out the ritual slametan Memitu was as a manifestation of gratitude for all the favors that had been given from the "Invisible Power" and also the hope of the smooth birth process. Express gratitude and the request is addressed to those considered to have the power to determine the smooth process of birth. In ritual slametan Memitu, there are theological dimensions that can be identified as belief in Invisible Substance and values for living in harmony together among residents of Kedungsana Village community. The theological dimensions in the earth alms ritual have been developed in such a way as to be in line with the development of social reality.Indonesia sangat terkenal dengan kekayan kebudayannya. Cirebon sebagai salah satu kabupaten di Jawa Barat juga sangat kental dengan budayanya. Artikel ini membahas salah satu budaya di Desa Kedungsana Cirebon yaitu fenomena tradisi ritual slametan Memitu.  Tujuan dari penelitian ini adalah untuk meneliti praktek ritual Memitu yang dilakukan oleh masyarakat Kedungsana bersama dengan dimensi-dimensi teologisnya. Subjek penelitian adalah komunitas masyarakat Desa Kedungsana Kecamatan Plumbon Kabupaten Cirebon. Proses pengumpulan data dilakukan dengan observasi langsung, untuk pendalaman dilakukan wawancara dengan teknik purposive sampling. Hasil penelitian ditemukan bahwa tujuan dilaksanakannya ritual slametan Memitu adalah sebagai manifestasi syukur atas segala nikmat yang telah diberikan dari “Kekuatan Tak Terlihat” dan juga pengharapan kelancaran proses kelahiran. Ungkapan rasa syukur dan permohonan tersebut ditujukan kepada yang diyakini memiliki kekuatan untuk menentukan kelancaran proses kelahiran. Dalam ritual slametan Memitu terdapat dimensi-dimensi teologi yang dapat diidentifikasi sebagai kepercayaan terhadap Zat Yang Gaib dan nilai-nilai untuk hidup rukun berdampingan antar-warga masyarakat Kelurahan Kedungsana.  Dimensi-dimensi teologis dalam ritual sedekah bumi ini telah dikembangkan sedemikian rupa agar sejalan dengan perkembangan realitas sosial.